EVERYDAY RELIGION: TAWARAN METODE PENELITIAN SOSIAL BAGI PENGEMBANGAN STUDI ISLAM - Karman Karman (Jurnal Studi Islam, 2022)
Religion in contemporary sociological studies does not only talk about official discourse, but also everyday lived. This paper describes "everyday lived" or "live religion". Through qualitative approaches and descriptive methods can be explained, religion and spirituality based on everyday lived can be analyzed through ordinary people in their daily religious practices. Everyday religion displays a different dynamic, which is freer from political construction. Everyday religion views agency as important, without neglecting structure. Structure refers to the ability of institutions to produce (and enforce) a pattern of meaning and action; agency refers to the individual or collective ability to improvise and bring alternatives to life. The study of "lived religion" can be an inspiration for the development of Islamic studies in various Islamic universities, especially the studies of the Qur'an and Hadith.Agama dalam kajian sosiologi kontemporer tidak semata-mata membicarakan official discourse, melainkan everyday lived. Tulisan ini mendeskripsikan "everyday lived" atau "live religion". Melalui pendekatan kualitatif dan metode deskriptif dapat dijelaskan, agama dan sipiritualitas berdasarkan everyday lived dapat dianalisis melalui orang-orang biasa dalam praktik keagamaan sehari-hari. Everyday religion menampilkan dinamika yang berbeda, yang lebih bebas dari konstruksi politik. Everyday religion memandang penting agensi, tanpa mengabaikan struktur. Struktur mengacu pada kemampuan lembaga untuk memproduksi (dan memaksakan) suatu pola pemaknaan dan tindakan; agensi mengacu pada kemampuan individu atau kolektif untuk melakukan improvisasi dan menghidupkan alternatif-alternatif. Studi "lived religion" dapat menjadi inspirasi bagi pengembangan studi Islam di berbagai perguru-an tinggi Islam, terutama kajian-kajian Al-Qur'an dan Hadis.